2019
DOI: 10.1246/cl.190306
|View full text |Cite
|
Sign up to set email alerts
|

Reduction-resistant [Au25(cyclohexanethiolate)18]0 with an Icosahedral Au13 Core

Abstract: Cyclohexanethiolate-protected gold cluster Au 25 (c-HT) 18 was isolated for the first time as a minor byproduct of [Au 23 (c-HT) 16 ] ¹. Single-crystal X-ray structure analysis revealed that Au 25 (c-HT) 18 has an icosahedral Au 13 core, in sharp contrast to the face-centered cubic cores in major products such as [Au 23 (c-HT) 16 ] ¹ and Au 28 (c-HT) 20. Au 25 (c-HT) 18 prefers a neutral state to an anionic state, probably because the Au 13 core is forced to deform due to the steric hindrance between the c-HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In the overall star-shaped architecture of the gold core (Fig. 4a ), Au–Au bond lengths followed the order: Au cent –Au inn > Au inn –Au inn > Au inn –Au out , as previously reported for other icosahedral Au 25 NCs 43 45 .
Fig.
…”
Section: Resultssupporting
confidence: 79%
“…In the overall star-shaped architecture of the gold core (Fig. 4a ), Au–Au bond lengths followed the order: Au cent –Au inn > Au inn –Au inn > Au inn –Au out , as previously reported for other icosahedral Au 25 NCs 43 45 .
Fig.
…”
Section: Resultssupporting
confidence: 79%
“…SCXRD showed that a new cluster, PtAu 24 (ScHex) 18 produced in entry 14, has an icosahedral MAu 12 core with six electrons . This structural motif does not follow the empirical rule that the metallic core prefers face-centered-cubic packing when bulky secondary thiols, such as ScHex, were used as the protecting ligands. , We recently reported that the pure Au 25 (ScHex) 18 cluster also possesses an icosahedral motif . These results illustrate the magic stability of the icosahedral core in MAu 24 (SR) 18 regardless of the stress from the steric repulsion between the bulky cyclohexyl ligands.…”
Section: Results and Discussionmentioning
confidence: 91%
“…In addition to the chemical composition of the cluster, the stability, electronic structure, and functions of Au n (SR) m clusters change depending on the functional-group structure of the ligand. 9,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] For example, it has been demonstrated that properties of Au 25 (SR) 18 , such as the stability in solution, reducibility, dissociation pattern under laser irradiation, quantum yield of photoluminescence, and catalytic activity, along with other properties, differ depending on the functional-group structure of the ligand. Therefore, the selection of the ligand functional group is essential in the functionalization of Au n (SR) m clusters.…”
Section: Introductionmentioning
confidence: 99%